Stres Akademik Sebagai Determinan Kualitas Tidur Remaja di Madrasah Aliyah - Hazimah Mufidah; Muhammad Ali Maulana; Yoga Pramana; Gabby Novikadarti Rahmah; Mita Mita (FORIKES, 2024)
Sleep disorders constitute one of the health problems that many adolescents face. Adolescents’ bedtime activities and routines may have an impact on sleep quality. The aim of this study was to analyze the relationship between academic stress and sleep quality of adolescents in madrasah aliyah. This study applied a cross-sectional design involving 91 adolescents in Madrasah Aliyah Negeri 2 Pontianak, who were selected using stratified random sampling. Academic stress and sleep quality of adolescents were measured using questionnaires namely Pittsburgh Sleep Quality Index (PSQI) for sleep quality and Educational Stress Scale for Adolescents (ESSA) for academic stress. The collected data were analyzed using the Spearman correlation test. The results of the analysis show that the p-value was 0.020 (there was significantly correlation) and the r-value was 0.244 (weak correlation level). It was thus concluded that academic stress was a determinant for the sleep quality of adolescents in Madrasah Aliyah Negeri 2 Pontianak.Keywords: adolescents; academic stress; sleep quality ABSTRAK Gangguan tidur merupakan salah satu masalah kesehatan yang banyak dihadapi oleh remaja. Aktivitas dan rutinitas sebelum tidur remaja mungkin berdampak pada kualitas tidur. Tujuan dari penelitian ini yaitu menganalisis hubungan antara stres akademik dan kualitas tidur remaja di madrasah aliyah. Penelitian ini menerapkan rancangan cross-sectional yang melibatkan 91 remaja di Madrasah Aliyah Negeri 2 Pontianak, yang dipilih menggunakan stratified random sampling. Stres akademik dan kualitas tidur remaja diukur menggunakan kuesioner yaitu Pittsburgh Sleep Quality Index (PSQI) untuk kualitas tidur dan Educational Stress Scale for Adolescents (ESSA) untuk stres akademik. Data yang terkumpul dianalisis menggunakan uji korelasi Spearman. Hasil analisis menunjukkan bahwa nilai p adalah 0,020 (ada korelasi secara signifikan) dan nilai r adalah 0,244 (tingkat korelasi lemah). Dengan demikian disimpulkan bahwa stres akademik merupakan determinan bagi kualitas tidur remaja di Madrasah Aliyah Negeri 2 Pontianak.Kata kunci: remaja; stres akademik; kualitas tidur